Giant milkweed (Calotropis gigantea): A new plant resource to inhibit protozoa and decrease ammoniagenesis of rumen microbiota in vitro without impairing fermentation - Ayemele, A.G.; Ma, L.; Park, T.; Xu, J.C.; Yu, Z.T.; Bu, D.P. (Elsevier, 2020)
This study screened six different species of forest plants and then further evaluated the most promising plant, giant milkweed (Calotropis gigantea), for the potential to improve nitrogen utilization efficiency (NUE) through inhibiting rumen protozoa in vitro. Ground leaves of giant milkweed at 1.6 and 3.2 mg/mL decreased the counts of Entodinium cells by 41.30% and 58.89%, respectively, and damaged their cell surface structure. Dasytricha, Isotricha, Epidinium, Ophryoscolex, and Diplodinium were not affected, while total bacterial and archaeal populations did not decrease. Ammonia nitrogen (NH3-N) concentration decreased by 50.64% and 33.33% at 1.6 g/mL and 3.2 mg/mL, respectively. Volatile fatty acid (VFA) production and methane production remained unaffected, but butyrate production increased. The giant milkweed leaves contained (per gram of dry matter) 3636 μg phenolics including 205.9 μg of 3-hydroxybenzoic acid, 2079 μg flavonoids including 1197.5 μg of quercetin and 91.4 μg of myricetin, and 490 μg alkaloids including 219.8 μg of anthraquinone glycosides. The effective inhibition of Entodinium was accompanied by a decrease in NH3-N concentration, and methane production did not increase except for the dose of 1.6 mg/mL. Giant milkweed may be used as a new feed additive or an alternative to chemicals or antibiotics for sustainable animal husbandry enhancing NUE in ruminants.